2016
DOI: 10.1186/s40064-016-3011-x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Enterobacter aerogenes septicemia in healthcare workers

Abstract: Enterobacter aerogenes is recognized as an important bacterial pathogen in hospital-acquired infections. This report describes two unusual cases of septicemia caused by E. aerogenes in immunocompetent healthcare workers. E. aerogenes was isolated from blood cultures of the two patients experiencing septicemia. The clinical isolates were initially identified as E. aerogenes using a VITEK II automated system and 16S rRNA sequence analysis, and; both isolates involved in the outbreak shared a common pulse-field g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…In addition, it has been isolated from patients with urinary tract infection (MENEZES et al, 2004) and from the water from bathroom taps of a higher education institution (OLIVEIRA FILHA et al, 2018), depicting its detrimental effect on public health. Jha et al (2016) reported that K. aerogenes was an important pathogen in acquired hospital infections. In a study assessing the urine of dogs and cats with clinical suspicion of urinary infection, Carvalho et al (2014) isolated K. aerogenes, showing its importance, as the animal can be infected by consuming food sold in bulk.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been isolated from patients with urinary tract infection (MENEZES et al, 2004) and from the water from bathroom taps of a higher education institution (OLIVEIRA FILHA et al, 2018), depicting its detrimental effect on public health. Jha et al (2016) reported that K. aerogenes was an important pathogen in acquired hospital infections. In a study assessing the urine of dogs and cats with clinical suspicion of urinary infection, Carvalho et al (2014) isolated K. aerogenes, showing its importance, as the animal can be infected by consuming food sold in bulk.…”
Section: Resultsmentioning
confidence: 99%
“…Gharieb et al (2013) investigated bacteria in wild birds from various locations in Egypt and isolated E. aerogenes and E. cloacae. In humans, E. aerogenes and E. cloacae have been reported in hospitals as important opportunistic pathogens, causing sepsis in neonates (Akindolire et al 2016, Köse et al 2016, Boulos et al 2017, nosocomial infection (Oliva-Menacho et al 2016), and septicemia in health professionals (Jha et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Otorkpa; IJPR, 2(3): [1][2][3][4][5][6][7][8][9]2019; Article no.IJPR. 48518 2 a good number of the drinking water presented as safe for consumption across Nigeria are actually not fit for human consumption.…”
Section: Fig 1 Common Sources Of Drinking Water In Nigeriamentioning
confidence: 99%
“…Enterobacter aerogenes is a Gram-negative, rodshaped bacterium usually found in the human gastrointestinal tract and does not generally cause disease in healthy individuals but recognized as an important bacterial pathogen in hospital-acquired infections and opportunistic infections [9]. This organism was isolated in 40% of the studies that analysed drinking water samples.…”
Section: Enterobacter Aerogenesmentioning
confidence: 99%